Triazatruxene: A Rigid Central Donor Unit for a D–A3 Thermally Activated Delayed Fluorescence Material Exhibiting Sub‐Microsecond Reverse Intersystem Crossing and Unity Quantum Yield via Multiple Singlet–Triplet State Pairs. Issue 6 (16th April 2018) - dos Santos, Paloma L.; Ward, Jonathan S.; Congrave, Daniel G.; Batsanov, Andrei S.; Eng, Julien; Stacey, Jessica E.; Penfold, Thomas J.; Monkman, Andrew P.; Bryce, Martin R.
Abstract: By inverting the common structural motif of thermally activated delayed fluorescence materials to a rigid donor core and multiple peripheral acceptors, reverse intersystem crossing (rISC) rates are demonstrated in an organic material that enables utilization of triplet excited states at faster rates than Ir‐based phosphorescent materials. A combination of the inverted structure and multiple donor–acceptor interactions yields up to 30 vibronically coupled singlet and triplet states within 0.2 eV that are involved in rISC. This gives a significant enhancement to the rISC rate, leading to delayed fluorescence decay times as low as 103.9 ns. This new material also has an emission quantum yield ≈1 and a very small singlet–triplet gap. This work shows that it is possible to achieve both high photoluminescence quantum yield and fast rISC in the same molecule. Green organic light‐emitting diode devices with external quantum efficiency >30% are demonstrated at 76 cd m −2 . Abstract : Initially, it was assumed that achieving a vanishingly small singlet‐triplet gap to maximize reverse intersystem crossing (rISC) in thermally activated delayed fluorescence (TADF) would inevitably lead to negligible fluorescence quantum yield (PLQY). Here, it is shown that through multiple singlet‐triplet states, both fast rISC >1 × 10 7 s ‐1 and PLQY 1 can be realized in a D–A3 molecule, a milestone for TADF.